Albert Camus’ La Peste and the COVID-19 Pandemic: Exile and Imprisonment, Suffering and Death, Defiance and Heroism - Salcedo, Francis Xavier R. (Journal for the study of religions and ideologies, 2020)
Albert Camus’ novel La Peste has once again sparked the interest and imagination of readers in lieu of the COVID-19 pandemic. Considering the existential trajectory of Camus’ philosophy, this paper argues that his milieu dialogues with our present context in a very timely and particular way. To present his philosophy as reflected in La Peste is therefore an interesting inquiry considering his distinctive analysis of the different secular and religious responses of the characters to the plague which, in many ways, reflect the current responses of world societies towards the COVID-19 pandemic. In light of humanity’s desire to find ways to overcome the COVID-19 pandemic and manage its aftermath, this paper attempts to articulate the relevance of Camus’ thoughts on defiance and heroism in facing the reality of exile, imprisonment, suffering and death. In doing so, I propose to analyze Camus’ philosophy in La Peste in relation to the COVID-19 pandemic. The whole analysis will revolve around the central themes of La Peste namely Exile and Imprisonment, Suffering and Death, Defiance and Heroism. Likewise, this reading of Camus’ notions in La Peste in relation to the COVID-19 pandemic brings to dialogue the traditional tension between preserving oneself from the consequences of an environmental crisis and reaching out to others despite the risks it entails.